Combined Elastic and Limit Analysis for Seismic Vulnerability Assessment of Pitched Portal Frames - Marco Postiglione; Fabio De Angelis; Giuseppe Brandonisio (Buildings)
This paper presents a combined approach for the seismic vulnerability assessment of pitched portal frames by coupling elastic and limit analysis. Pitched portal frames are widely adopted both in civil and industrial building structures, as well as in architectural heritage structures, including cathedral portal frames in ecclesiastical buildings. The seismic vulnerability assessment of such structures is crucial for mitigating territorial seismic risk. In this study, elastic and limit analyses are adopted and combined to evaluate the seismic capacity of pitched portal frames. To this end, a simplified model is proposed to analyze both linear and non-linear responses of these structures under horizontal actions. Although the analysis focuses on two-dimensional (2D) portal frames, it can be extended to three-dimensional (3D) buildings in a straightforward manner due to the specific characteristics of the analyzed structural scheme. The proposed approach provides a preliminary yet efficient evaluation of the seismic vulnerability of buildings with pitched portal frames. Furthermore, the effectiveness of the proposed procedure ensures valuable applicability in large-scale seismic assessments.